La propagande de recrutement militaire au Canada, 1914-1917: essai en histoire des mentalités - Pinsonneault, Gérard (Université de Sherbrooke, 1981)
Keywords: Armée

Histoire du 65e régiment carabiniers Mont-Royal - Chambers, Ernest J. (s.é., 1906)
Keywords: Fusiliers Mont-Royal; Milice

A la recherche de l'histoire vraie - Pouliot, Adrien (La revue de l'Université Laval, 1961)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

L'invasion du Canada en 1775, d'après les historiens canadiens-français - Kelly, John E. (Université Laval, 1941)
Keywords: Américains; Armée; Historiens

La famille Céloron de Blainville - Roy, P.-G. (Bulletin des recherches historiques, 1909)
Keywords: Céloron de Blainville (famille)

De la Nouvelle-Angleterre à la Nouvelle-France: l'histoire des captifs anglo-américains au Canada entre 1675 et 1760 - Fournier, Marcel (Société généalogique canadienne-française, 1992)
Keywords: Américains; Captifs

De Montréal (en Bugey) à Montréal (au Canada) - Gauthier, Pierre (Revue d'histoire de l'Amérique française, 1949)
Keywords: Douglas (famille)

Frontenac vs l'abbé de Fénelon, une tragi-comédie judiciaire - Groulx, Lionel (Revue d'histoire de l'Amérique française, 1958)
Keywords: Communautés religieuses; Salignac de La Mothe Fénelon, François de; Sulpiciens

The Montreal Militia as a Social Institution before World War I - Miller, Carman (Urban History Review / Revue d'histoire urbaine, 1990)
Keywords: Milice

Annaotaha et Dollard vus de l'autre côté de la palissade - Dickinson, John A. (Revue d'histoire de l'Amérique française, 1981)
Keywords: Annaotaha, Etienne; Autochtones; Dollard Des Ormeaux, Adam

L'exploit du Long-Sault - ses motifs - ses résultats - Pouliot, Adrien (Revue d'histoire de l'Amérique française, 1969)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

L'Affaire "Dollard", de Fort Orange au Long-Sault - Rousseau, Jacques (Revue d'histoire de l'Amérique française, 1960)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

L'Université de Montréal et sa participation à la Deuxième Guerre mondiale - Lafontaine, Gilles (Université de Montréal, 1985)
Keywords: Guerre; Université de Montréal

An Imperial Garrison in its Colonial Setting. British Regulars in Montreal, 1832-1854 - Senior, Elinor Kyte (Université McGill, 1976)
Keywords: Armée; Britanniques; Garnison

Louis-Hector de Callières, gouverneur de Montréal. Aspect militaire 1684-1698 - Sigouin-Pigeon, Alice (Université d'Ottawa, 1969)
Keywords: Callière, Louis-Hector de; Gouverneurs

FLEMING, JOHN - Deslauriers, Peter (Dictionnaire biographique du Canada, 1987)

The Fortifications of Montreal 1717-1744: the Development and Implementation of the Plan - Poirier, Monique (Université Concordia, 1991)
Keywords: Fortifications

Entente cordiale? La section montréalaise du Fonds patriotique canadien, 1914-1923: le bénévolat de guerre à Montréal - Morton, Desmond (Revue d'histoire de l'Amérique française, 1999)
Keywords: Bénévolat; Guerre

De Jeanne D'Arc à Madeleine de Verchères: la femme guerrière dans la société d'Ancien Régime - Gervais, Diane; Lusignan, Serge (Revue d'histoire de l'Amérique française, 1999)
Keywords: Combat; Femmes; Forts

Un cadet de Gascogne: Philippe de Rigaud de Vaudreuil - Frégault, Guy (Revue d'histoire de l'Amérique française, 1951)
Keywords: Gouverneurs; Rigaud de Vaudreuil, Philippe de

Les drapeaux militaires en Nouvelle-France - Chartrand, René (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Keywords: Armée

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Les milieux d'affaires francophones de Montréal face à la Première Guerre mondiale - Villerbu, Tangi (Université de Rennes 2, 1996)
Keywords: Francophones; Guerre; Hommes d'affaires

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

Le mouvement ouvrier montréalais et la crise de la conscription 1916-1918 - Dansereau, Bernard (Université du Québec à Montréal, 1994)
Keywords: Conscription; Guerre

Les troupes de la marine, 1683-1713 - Russ, Christopher John (Université McGill, 1971)
Keywords: Armée

Les quatre couleurs de Radisson: explorer aujourd'hui le XVIIe siècle - Fournier, Martin (Université Laval, 1998)

Guerre et censure: l'expérience des journaux, des militaires et de la population pendant la Deuxième Guerre mondiale - Beauregard, Claude (Université Laval, 1995)
Keywords: Guerre; Journalistes

L’opinion canadienne devant la guerre de 1914 - Héroux, Maurice (Université de Montréal, 1952)
Keywords: Guerre

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs

Francois Marie Perrot and the Isle Perrot - Scott Wardleworth, Eleanor (Université McGill, 1931)
Keywords: Perrot, François-Marie

Le billet de Dollard - Dumas, Sylvio (La revue de l'Université Laval, 1960)
Keywords: Dollard Des Ormeaux, Adam

Gloire et respect à Dollard - Lanctot, Gustave (La revue de l'Université Laval, 1960)
Keywords: Dollard Des Ormeaux, Adam

The Montreal Irish and the Great War - Burns, Robin S. (Canadian Catholic Historical Association, Study Sessions, 1985)
Keywords: Guerre; Irlandais

La capitulation de Montréal, 8 septembre 1760 - Perrault, Claude (Cahiers de Sainte-Marie, 1967)
Keywords: Capitulation

McGill University at War, 1914-1918, 1939-1945 - Fetherstonhaugh, R. C. (Université McGill, 1947)
Keywords: Guerre; Mortalité; Université McGill

The Montreal Highland Cadets - Chambers, Ernest J. (Desbarats, 1901)
Keywords: Milice; Montreal Highland Cadets

History of the 65th Mount Royal Rifles - Chambers, Ernest J. (D. Fleshman, 1988)
Keywords: Milice; Mount Royal Rifles

Évolution de la profession médicale au Québec: La contribution militaire de Laval à Montréal - Desjardins, Édouard (L'Union médicale du Canada, 1975)
Keywords: Guerre; Médecine; Université de Laval à Montréal

L'affaire du Long-Sault: valeur des sources iroquoise et française - Vachon, André (Les Cahiers des Dix, 1975)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Michel-Sidrac Dugué, sieur de Boisbriand - Sulte, Benjamin (Bulletin des recherches historiques, 1904)
Keywords: Dugué de Boisbriand, Michel-Sidrac

Philippe de Rigaud de Vaudreuil, Governor of New France 1703-1725 - Zoltvany, Yves F (McClelland and Stewart, 1974)
Keywords: Gouverneurs; Rigaud de Vaudreuil, Philippe de

Les Gouverneurs de Montréal (1642-1760) - Roy, P.-G. (Les Cahiers des Dix, 1942)
Keywords: Gouverneurs

Nicolas Blaise des Bergères de Rigauville - Roy, P.-G. (Bulletin des recherches historiques, 1916)
Keywords: Blaise Des Bergères de Rigaudville, Nicolas

Raymond Blaise des Bergères - Roy, P.-G. (Bulletin des recherches historiques, 1916)
Keywords: Blaise Des Bergères de Rigaudville, Raymond

L'Affaire du Long-Sault: valeur de la source huronne - Vachon, André (La revue de l'Université Laval, 1963)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Who Shall Separate Us?: The Montreal Irish and the Great War - Burns, Robin S. (The Untold Story: The Irish in Canada, 1988)
Keywords: Guerre; Irlandais

Roots of the Canadian Army; Montreal District, 1846-1870 - Senior, Elinor Kyte (The Society of the Montreal Military and Maritime Museum / La Société du musée militaire et maritime de Montréal, 1981)
Keywords: Armée; Milice

The Fenian Invasion of Canada of 1866 and 1870 and the Operations of the Montreal Militia Brigade in Connection Therewith - Campbell, F. W. (s.é., 1904)
Keywords: Féniens; Milice

British Regulars in Montreal: An Imperial Garrison, 1832-1854 - Senior, Elinor Kyte (McGill-Queen's University Press, 1981)
Keywords: Armée; Britanniques; Garnison

The British Garrison in Montreal in the 1840's - Senior, Elinor Kyte (Journal of the Society for Army Historical Research, 1974)
Keywords: Armée; Britanniques; Garnison

Provincial Troops in the Montreal Area 1775-1784 - Fryer, Mary Beacock (The Loyalists of Quebec 1774-1825: A Forgotten History, 1989)
Keywords: Loyalistes

The British Army and Sport in Canada: Case Studies of the Garrison of Halifax, Montreal and Kingston to 1871 - Day, Robert Douglas (Université d'Alberta, 1981)
Keywords: Armée; Britanniques; Garnison

Jacques Bizard, major de Montréal - Roy, P.-G. (Bulletin des recherches historiques, 1916)
Keywords: Bizard, Jacques

L'exploit du Long-Sault. Les témoignages des contemporains - Pouliot, Adrien; Dumas, Sylvio (Société historique de Québec, 1960)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Josué Boisberthelot de Beaucours - Roy, P.-G. (Bulletin des recherches historiques, 1904)
Keywords: Dubois Berthelot de Beaucours, Josué; Gouverneurs

Quand Saint-Sulpice allait en guerre... - Maurault, Olivier (Les Cahiers des Dix, 1940)
Keywords: Communautés religieuses; Sulpiciens

Les Sabrevois, Sabrevois de Sermonville et Sabrevois de Bleury - Massicotte, E.-Z. (Bulletin des recherches historiques, 1925)
Keywords: Sabrevois de Bleury, Clément de; Sabrevois de Sermonville, Christophe de; Sabrevois, Jacques-Charles de

Dollard des Ormeaux et ses compagnons. Notes et documents - Massicotte, E.-Z. (Le Comité du Monument Dollard des Ormeaux, 1920)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Le Sieur La Fresnaye de Brucy - Massicotte, E.-Z. (Bulletin des recherches historiques, 1930)
Keywords: La Fresnaye de Brucy, Antoine de

Dominique de La Motte, sieur de Lucière - Massicotte, E.-Z. (Bulletin des recherches historiques, 1921)
Keywords: La Motte de Lucière, Dominique de

Madame Bois Berthelot de Beaucours - Massicotte, E.-Z. (Bulletin des recherches historiques, 1915)
Keywords: Aubert de La Chesnaye, Françoise; Dubois Berthelot de Beaucours, Josué; Gouverneurs

Perrot, neveu de Talon, deuxième gouverneur de Montréal - Malchelosse, Gérard (Les Cahiers des Dix, 1942)
Keywords: Gouverneurs; Perrot, François-Marie

Montréal sous la menace iroquoise - Gyger, Tony (L'Hôtel-Dieu de Montréal 1642-1973, 1973)
Keywords: Autochtones; Iroquois

De la Champagne à la Nouvelle-France, Claude de Ramesay (1659-1724) - Litalien, Raymonde (Catalogue de l'exposition Le Canada de Louis XIV, 1980)
Keywords: Gouverneurs; Ramezay, Claude de

Le dossier de Dollard: la valeur des sources, la grandeur du dessein, la grandeur du résultat - Groulx, Lionel (Imprimerie populaire, 1932)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Dollard est-il un mythe? - Groulx, Lionel (Fides, 1960)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Lueurs guerrières sur le Long Sault - Pouliot, Adrien (La revue de l'Université Laval, 1960)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

La menace iroquoise, de 1657 à 1660 - Pouliot, Adrien (La revue de l'Université Laval, 1961)
Keywords: Autochtones; Dollard Des Ormeaux, Adam; Iroquois

Ville-Marie décide l'offensive - Pouliot, Adrien (La revue de l'Université Laval, 1961)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Pierre Le Moyne d'Iberville - Frégault, Guy (Fides, 1968)
Keywords: Le Moyne d'Iberville et d'Ardillières, Pierre

Iberville le conquérant - Frégault, Guy (Éditions Pascal, 1944)
Keywords: Le Moyne d'Iberville et d'Ardillières, Pierre

Pierre You et son fils François d'Youville - Ferland-Angers, Albertine (Thérien, 1941)
Keywords: Fourrure; You, Pierre; Youville, François d'

Dollard des Ormeaux dans les textes - Desrosiers, Léo-Paul (Les Cahiers des Dix, 1945)
Keywords: Dollard Des Ormeaux, Adam

Lemoyne d'Iberville: A Soldier of New France - Crouse, Nellis Maynard (The Ryerson Press/Cornell University Press, 1954)
Keywords: Le Moyne d'Iberville et d'Ardillières, Pierre

Un Bourguignon, Gouverneur de Montréal: Jean Bouillet de La Chassaigne - Demaiziere, E. (Nova Francia, 1925)
Keywords: Bouillet de La Chassaigne, Jean; Gouverneurs

Guérillas dans l'île de Montréal - Desrosiers, Léo-Paul (Les Cahiers des Dix, 1966)

Un défenseur de la Nouvelle-France, François Piquet, le "Canadien" (1708-1781) - Chagny, André (Librairie Emmanuel Vitte, 1913)
Keywords: Autochtones; Communautés religieuses; Missions; Piquet, François; Sulpiciens

Mort de M. de la Gauchetière - Fauteux, Aegidius (Bulletin des recherches historiques, 1931)
Keywords: Migeon de La Gauchetière, Daniel

The Lake Champlain Army and the Fall of Montreal - Charland, Thomas (Vermont History, 1960)
Keywords: Armée

Dollard des Ormeaux - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1912)
Keywords: Dollard Des Ormeaux, Adam

Les compagnons de Dollard des Ormeaux - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1913)
Keywords: Dollard Des Ormeaux, Adam

La thèse de la course aux fourrures - Pouliot, Adrien (La revue de l'Université Laval, 1961)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Malachi James at the Fall of Montreal, 1760 - Howe, Henry Forbush (Proceedings of the Massachusetts Historical Society, 1950)
Keywords: Capitulation; James, Malachi

Où fut signée la capitulation de Montréal? - Massicotte, E.-Z. (Bulletin des recherches historiques, 1940)
Keywords: Capitulation

La milice de 1663 - Massicotte, E.-Z. (Bulletin des recherches historiques, 1926)
Keywords: Milice

Les officiers d'état-major des gouvernements de Québec, Montréal et Trois-Rivières sous le régime français - Roy, P.-G. (Revue canadienne, 1917)
Keywords: Armée

Les armes des premiers colons de Montréal - Massicotte, E.-Z. (Bulletin des recherches historiques, 1939)
Keywords: Armes

Dollard Des Ormeaux and the Fight at Long Sault: Was Dollard the Saviour of New France? - Lanctot, Gustave (Canadian Historical Review, 1932)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

New England Captives carried to Canada between 1677 and 1760 during the French and Indians wars - Coleman, E. L. (Southwoth Press, 1925)
Keywords: Autochtones; Captifs; Guerre

The Provincial Cavalry in Lower Canada 1837-50 - Senior, Elinor Kyte (Canadian Historical Review, 1976)
Keywords: Milice

Dollard des Ormeaux and the Fight at the Long Sault: A re-interpretation of Dollard's Exploit - Adair, E. R. (Canadian Historical Review, 1932)
Keywords: Autochtones; Dollard Des Ormeaux, Adam

Les forts et fortifications de Montréal - Garant, Jean-Marc (Cahier de la Société historique de Montréal, 1984)
Keywords: Fortifications; Forts

La redoute de Dollard à la Baie des Sauvages. Un fort défendu par dix-sept Français - Barbeau, Marius (Revue canadienne de géographie, 1959)
Keywords: Autochtones; Dollard Des Ormeaux, Adam